Evidence of pinning crossover and the role of twin boundaries in the peak effect in FeSeTe iron based superconductor. (5th December 2017) - Galluzzi, A; Buchkov, K; Tomov, V; Nazarova, E; Leo, A; Grimaldi, G; Nigro, A; Pace, S; Polichetti, M
Abstract: The correlation between the appearance of a peak effect in the critical current of a superconducting material and the presence of twin boundaries, involved in a crossover between different pinning regimes, is investigated by means of dc magnetic measurements on a FeSe0.5 Te0.5 crystal. In particular, by analyzing the temperature dependence of the critical current density J c ( T ) for different magnetic fields H, a crossover from a weak pinning regime to a strong pinning regime has been revealed. The analysis shows that this crossover can be ascribed to the presence of twin boundary defects inside the sample, and can be associated to the onset of the peak effect and interpreted as the start of the vortex dynamic processes responsible for the increase of J c with the field. On the basis of the information extracted by our analysis, a plausible dynamic scenario involving the contribution of the different pinning regimes depending on the applied field has been described, and the relative H ( T ) vortex phase diagram has been determined. Moreover, in our description, the peak in the J c ( H ) curve corresponds to the end of the processes leading to the peak effect and it is confirmed to be related to the transition from an elastic to a plastic deformation regime in the vortex lattice.